76.8k views
4 votes
What is the sum? 2x/x2 + x-4/9x

User Yesthatguy
by
4.7k points

1 Answer

3 votes

Answer:

(x² + 14x)/(9x²)

Explanation:

To do this calculation process:

The first term: 2x/x² = 2/x.

Then: (2/x) + (x - 4)/(9x).

We should common the denominator by multiplying the denominators of the two terms (9x)(x) = 9x² and dividing each denominator by the common denominator.

So, it will be equal:

[(2)(9x) + (x - 4)(x)]/9x² = (18x + x² - 4x)/9x² = (x² + 14 x)/9x².

User Hakunamatata
by
4.8k points